Pengaruh Beban Kerja Dan Motivasi Terhadap Kinerja Pegawai Dinas Kependudukan Dan Catatan Sipil Di Kota Makassar - Mirna; Samsul Rizal; Andi Risfan Rizaldi (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The purpose of this study was to determine and analyze the effect of workload and motivation on the performance of population and civil registration service employees in Makassar City. The type of research used is a quantitative descriptive research method, with 54 respondents. Data collection techniques used in this study were observation, questionnaires, and documentation. The data analysis technique used was statistical calculations through the Statistical for the Social Science (SPSS) version 22 application. This can be seen from the results of SPSS data processing where the workload variable (X1) has a t count of 1.868 while the t table is 1.675 and a sig value of 0.05. This shows that t count > t table (1.868 > 1.675) and sig value of 0.068 > 0.05. This means that the workload variable has a positive but insignificant effect on employee performance. The motivation variable (X2) has a t count of 5.088 while the t table is 1.675 and a sig value of 0.05. This shows that the t count test > t table (5.088 > 1.675) and a sig value of 0.00 < 0.05. This means that the motivation variable has a positive and significant effect on employee performance.